SORPTION AND SOLUBILITY OF LOW-SHRINKAGE RESIN-BASED DENTAL COMPOSITES - Sevda Yantcheva; Radosveta Vasileva (Peytchinski Publishing, 2016)
Background: Resin-based composites are well-established restorative materials. However, these materials may absorb significant amounts of water when exposed to aqueous environments. Sorption and solubility are affecting composite restorations by two different mechanisms; the first is the up taking of water producing an increased weight and the second is the dissolution of materials in water, leading to a weight reduction of the final conditioned samples. Objective: To measure the water sorption and solubility of different low-shrinkage resin-based composites. Six materials were selected: Filtek P60, Filtek Ultimate, SonicFill, Filtek Silorane, Kalore and Venus Diamond. Materials and methods: Five disc specimens were prepared of each material and polymerized with diode light-curing unit. Water sorption and solubility of the different materials were were calculated by means of weighting the samples before and after water immersion and desiccation. Data were statistically analyzed using Shapiro-Wilk One Way Analysis of Variance followed by the Holm-Sidak comparison test . Results: There were significant differences (p<=0.001) between materials regarding sorption and solubility. Regarding sorption F. Silorane showed lowest values, followed by SonicFill, without significant difference between them. Statistical significant differences exist between F. Silorane and F.P60, F. Ultimate, Kalore. Significant differences exist between SonicFill and F. Ultimate. F.Silorane (-0.018) and Kalore (-0.010) showed lowest values of solubility but there were marginal difference among all composites investigated. Conclusions: 1.The material with lowest values of sorption and solubility was F.Silorane. 2. The attained sorption and solubility values for composites are influenced by the differences in resin matrix composition and filler contend. 3. Modifications of dimethacrylate matrix did not minimize significantly sorption and solubility of composites. 4. Besides water sorption resin composites are stable structures: solubility is lower then sorption.